Molecular Evolution of New Species without Modern Synthetic Theory (neo-Darwinism) - Ahad, Md. Abdul (International Journal of Bio-resource and Stress Management, 2023)
The modern synthetic theory (neo-Darwinism) is an extension of Darwinian Theory of evolution. It is a combination of mutations and natural selection. Both Darwinian and synthetic theory are based on mutation and population genetics. This theory is accepted by the most biologists. It advocates that molecular evolution occurs through the changes of gene structure or frequency via the agents of this theory especially by mutation. But mutations are random changes of DNA. Most mutations are homozygous recessive and harmful. It inhibits metabolic processes and produces dangerous diseases as well as opposed molecular evolution of new species. If accidentally possible (either naturally or artificially), this change is might be within the species and form variety (or race or strain). But aquirring of status of this variety to a species is less possible due to segregation and failure to gain reproductive isolation.